Clarifying the costs of conflicts of interest. Issue 3 (March 2015) - Mayes, C.; Lipworth, W.; Kerridge, I.
<x xml:space="preserve">Abstract</x> Linked Comment: Citrome et al. Int J Clin Pract 2015; 69: 267–8. Linked Comment: Clark et al. Int J Clin Pract 2015; 69: 270–2. Linked Comment: Stossel et al. Int J Clin Pract 2015; 69: 385–6.